2018
DOI: 10.1007/s00405-018-4985-5
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphous adenocarcinoma of the salivary glands: reappraisal and update

Abstract: Although relatively rare, polymorphous adenocarcinoma (PAC) is likely the second most common malignancy of the minor salivary glands (MiSG). The diagnosis is mainly based on an incisional biopsy. The optimal treatment comprises wide surgical excision, often with adjuvant radiotherapy. In general, PAC has a good prognosis. Previously, PAC was referred to as polymorphous low-grade adenocarcinoma (PLGA), but the new WHO classification of salivary gland tumours has also included under the PAC subheading, the so-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 129 publications
(236 reference statements)
0
64
0
9
Order By: Relevance
“…The critical differential diagnosis on aspirates from metastatic sites is PTC . Presence of metachromatic matrix and flocculent mucoid material, with lack of colloid has been found to be useful in distinguishing CAMSG from PTC on FNA . We identified glomeruloid structures with a narrow stalk, recapitulating the histological features of CAMSG, which are only rarely described in PTC.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The critical differential diagnosis on aspirates from metastatic sites is PTC . Presence of metachromatic matrix and flocculent mucoid material, with lack of colloid has been found to be useful in distinguishing CAMSG from PTC on FNA . We identified glomeruloid structures with a narrow stalk, recapitulating the histological features of CAMSG, which are only rarely described in PTC.…”
Section: Discussionmentioning
confidence: 70%
“…Gailey et al reported the cytology of CAMSG in benchtop aspirates of a biopsy‐confirmed tongue CAMSG with nodal metastasis. They identified tumour cells in sheets, papillary fronds and tips, and occasional cribriform structures, accompanied by nuclear features of PTC and moderate amount of fluffy cytoplasm . Appukutty et al observed basaloid tumour cells in sheets, papillae and trabecular pattern in an upper cervical lymph node FNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Papillary configuration is frequently seen in many salivary neoplasms, e.g., WT, oncocytoma, polymorphous low-grade adenocarcinoma (nowadays, polymorphous adenocarcinoma, PAC; [49]), papillary cystadenoma, etc. Ductal papillomas comprise a special group of adenomas with unique papillary features.…”
Section: Sialadenoma Papilliferummentioning
confidence: 99%